Expositions of Plants in the Park of Sameda Vurgun on Absheron - Gulmammadova, Shalala Adil; Mammadov, Tofik Sadiq (Hortus botanicus, 2022)
The article describes the results of the taxonomical research of ornamental trees, shrubs and herbaceous plants from 23 families, of 32 genera and 35 species, the forms of expositions, rules of grouping plants in expositions, the use of small architectural forms of the Samed Vurgun Park. It was revealed that investigated plants adapt well in the Absheron conditions, are promising and it is recommended for the various expositions in parks, gardens and squares.